Damar agroforests in Sumatra, Indonesia: domestication of a forest ecosystem through domestication of dipterocarps for resin production - Foresta, H. de; Michon, G.; Kusworo, A.; Levang, P. (Center for International Forestry Research, 2004)
Farmers in the West Lampung Pesisir area in the south of Sumatra, Indonesia, have established forest gardens by introducing damar trees in upland rice swidden plantations. These damar gardens were established as the wild resource itself was vanishing. While cultivating this forest resorce, villagers have achieved the global restoration of a forest in the middle of agricultural lands. Harvest of resin from damar trees represents the main source of household cash income. Furthermore, Pesisir farmers managed to preserve a high level of biodiversity and a whole range of economic products and functions originally derived from the forest. Institutionally, appropriation of the forest resource entailed a total reorganization of the traditional tenure system for forest lands and goes along with the increasing importance of land as property and privatisation of this property. During the 1990s, the acceleration of regional development has threatened the agroforests area, as they were not recognized by the state and had no legal status. Damar gardens, as a succesful forest management strategy developed by local communities, may represent an important support for the development of formal recognition of local people's rights over forest resources.